Mutations in the Methyltransferase Motifs of L Protein Attenuate Newcastle Disease Virus by Regulating Viral Translation and Cell-to-Cell Spread - Xiao Li; Lu Sun; Jing Zhao; Kaihang Tu; Jia Xue; Xin Guo; Guozhong Zhang (Microbiology Spectrum, 2021)
ABSTRACT The large (L) polymerase proteins of most nonsegmented, negative-stranded (NNS) RNA viruses have conserved methyltransferase motifs, (G)-G-G-D and K-D-K-E, which are important for the stabilization and translation of mRNA. However, the function of the (G)-G-G-D and K-D-K-E motifs in the NNS RNA virus Newcastle disease virus (NDV) remains unclear. We observed G-G-D and K-D-K-E motifs in all NDV genotypes. By using the infection cloning system of NDV rSG10 strain, recombinant NDVs with a single amino acid mutated to alanine in one motif (G-G-D or K-D-K-E) were rescued. The intracerebral pathogenicity index and mean death time assay results revealed that the G-G-D motif and K-D-K-E motif attenuate the virulence of NDV to various degrees. The replication, transcription, and translation levels of the K-D-K-E motif-mutant strains were significantly higher than those of wild-type virus owing to their altered regulation of the affinity between nucleocapsid protein and eukaryotic translation initiation factor 4E. When the infection dose was changed from a multiplicity of infection (MOI) of 10 to an MOI of 0.01, the cell-to-cell spread abilities of G-G-D- and K-D-K-E-mutant strains were reduced, according to plaque assay and dynamic indirect immunofluorescence assay results. Finally, we found that NDV strains with G-G-D or K-D-K-E motif mutations had less pathogenicity in 3-week-old specific-pathogen-free chickens than wild-type NDV. Therefore, these methyltransferase motifs can affect virulence by regulating the translation and cell-to-cell spread abilities of NDV. This work provides a feasible approach for generating vaccine candidates for viruses with methyltransferase motifs. IMPORTANCE Newcastle disease virus (NDV) is an important pathogen that is widespread globally. Research on its pathogenic mechanism is an important means of improving prevention and control efforts. Our study found that a deficiency in its methyltransferase motifs (G-G-D and K-D-K-E motifs) can attenuate NDV and revealed the molecular mechanism by which these motifs affect pathogenicity, which provides a new direction for the development of NDV vaccines. In addition to the (G)-G-G-D and K-D-K-E motifs of many nonsegmented, negative-stranded RNA viruses, similar motifs have been found in dengue virus, Zika virus, Japanese encephalitis virus (JEV), and severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). This suggests that such motifs may be present in more viruses. Our finding also provides a molecular basis for the discovery and functional study of (G)-G-G-D and K-D-K-E motifs of other viruses.